Good Enough for Government Work? Life-Evaluation and Public Policy - Semple, Noel (2019)
A life-evaluation question asks a person to quantify his or her overall satisfaction with life, at the time when the question is asked. If the goal of public policy is to make individuals’ lives better, does it follow that maximizing aggregate life-evaluations constitutes policy success? This paper argues that life-evaluation data provides a solid basis for welfare-consequentialist policy-making. This is illustrated by the successful argument for expanding state-funded mental health services in the United Kingdom.However, life-evaluations do not always provide a complete account of individual welfare. Policy-makers therefore must sometimes inquire into the extent to which individuals’ preferences would be fulfilled, if different policies were to be adopted. This article proposes synthesizing life-evaluationist and preferentist data about individual welfare, as a basis for rational policy-making.
Keywords: Noel Semple